Analysis of TikTok Content @bellaclrs_ as a Brand Advocate in Building Credibility - Dewi Pratiwi Wahyu Ramadhani; Diana Amalia (Lavish Opulent Education, 2026)
The rapid growth of social media, particularly TikTok, has driven changes in marketing communication strategies and the development of influencer credibility in the digital space. This study aims to analyze how credibility is constructed through TikTok content on the @bellaclrs_ account as a brand advocate for fast fashion products. The research employs a descriptive qualitative approach using content analysis, referring to persuasive communication theory and Source Credibility Theory, which includes expertise, trustworthiness, and attractiveness. The data were obtained from TikTok posts featuring fashion product promotions. The findings indicate that @bellaclrs_’s credibility is consistently built through the representation of these three dimensions within the content. Expertise is reflected in the ability to present fashion references, trustworthiness is shown through message consistency and alignment, and attractiveness is conveyed through aesthetic visuals and engaging communication style. These findings suggest that influencer credibility is formed through consistent message construction in content, thereby supporting the role as a brand advocate in promoting fast fashion on TikTok.